PENGARUH KEPEMILIKAN MANAJERIAL, PROFITABILITAS DAN SET PELUANG INVESTASI PADA KEBIJAKAN UTANG - Yulia, Aida; Nurhaida, Nurhaida (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 10 No 2 (2015), 2015)
The objective of this research is to examine and analyze the effects of managerial ownership, profitability and investment opportunity set on debt policy from listed companies in the manufacturing sector in the Indonesia Stock Exchange method. The research by using purposive sampling and balanced panel data, there are 66 companies fulfilling the criteria. The data type used is secondary data gotten from the capital market reference center at the Indonesia Stock Exchange. The multiple regression analysis models is used to test hypothesis. The result of the research shows that managerial ownership has no impact on debt policy. Profitability measured by Return on Asset (ROA) has a negative influence on debt policy, and investment opportunity set measured by Market to Book Value of Equity (MBVE ) has a negative influence on debt policy.
Keywords: Managerial Ownership, Profitability, Investment Opportunity Set